The Effectiveness of Neem Cake (Azadirachta indica) Water Extract against Aphids (Aphis gossypii) on Red Chili Plant - Lathifah Azizah; Ceppy Nasahi; Danar Dono (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2021)
Aphis gossypii is one of the factors that reduce chili production which acts as a pest and virus vector. This research aimed to determine the effectiveness of the application of neem cake water extract to A. gossypii on red chili plants. This research consisted of 2 experimental stages, namely in the laboratory and the greenhouse trials. The experimental design in the laboratory used a completely randomized design of neem cake water extract with treatments is A (Control), B (0.3%), C (0.6%), D (1.2%), E (2.4%), F (4.8%). Each treatment replicate 4 times. Aplication of water neem cake extract by dipping method of chilli leaf. After the leaf feed air dried, then the leaf put into plastic box and invested with 10 nymph of A. gossypii. While the experiments in the greenhouse used a randomized block design of neem cake water extract treatments were A (Control), B (LC50), C (1.5xLC50), D (2xLC50), E (2.5xLC50), F (3xLC50). The concentration of neem extract in the greenhouse experiment based on result of experiment at laboratory. Adults of A. gossypii as much as 20 were invested on every red chili plant. Application of neem cake water extract on red chili plants once every 4 days. The results showed that neem cake water extract effective to A. Gossypii with 0.14% as LC50. Neem cake water extract at concentration of 1.5xLC50 (0.21%) was effective suppressing A. gossypii population on red chili plants.